2018
DOI: 10.1007/s10482-018-1123-8
|View full text |Cite
|
Sign up to set email alerts
|

Three new Leptographium spp. (Ophiostomatales) infecting hardwood trees in Norway and Poland

Abstract: Species of Leptographium are characterized by mononematous or synnematous conidiophores and are commonly associated with different arthropods. Some of them also produce a sexual state characterised by globose ascomata with elongated necks. Compared to investigations on coniferous trees, the occurrence of Leptographium species on hardwood trees has been poorly studied in Europe. During a survey of ophiostomatoid fungi on various hardwood tree species in Norway and Poland, three unusual species, which fit in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…The species were named Ceratocystiopsis synnemata and Leptographium alneum. The results confirm earlier findings that many species of the Ophiostomatales are associated with hardwoodinfesting bark beetles in Poland (Jankowiak et al 2017(Jankowiak et al , 2018(Jankowiak et al , 2019aAas et al 2018).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The species were named Ceratocystiopsis synnemata and Leptographium alneum. The results confirm earlier findings that many species of the Ophiostomatales are associated with hardwoodinfesting bark beetles in Poland (Jankowiak et al 2017(Jankowiak et al , 2018(Jankowiak et al , 2019aAas et al 2018).…”
Section: Discussionsupporting
confidence: 91%
“…However, the results of the present study confirm previous Polish investigations that some of the Leptographium species have a close affinity to hardwoods in Europe. Recently, L. betulae, L. tardum, and L. trypodendri were collected from hardwood-infesting bark beetles in Poland (Jankowiak et al 2017(Jankowiak et al , 2018, while three other Leptographium species have been isolated and formally described from hardwood wounds (Jankowiak et al 2018(Jankowiak et al , 2019c.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, relatively little is known regarding wound‐associated Ophiostomatales in European hardwood ecosystems. A recent report from Poland indicated that hardwoods are niches for these fungi (Jankowiak et al , ). Previously, a study conducted in Norway discovered three Ophiostoma species from hardwood wounds, including Ophiostoma borealis which was described as a new species (Kamgan Nkuekam et al , ).…”
Section: Introductionmentioning
confidence: 99%